2011
DOI: 10.1007/s10495-011-0602-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol

Abstract: One of characteristics of diabetes mellitus (DM) is endothelial cell (EC) dysfunction and apoptosis which contributes to the development of vasculopathy. Advanced glycation end products (AGEs) continuously produced in the setting of DM play an important role in causing EC dysfunction and apoptosis. However, the underlying molecular mechanism remains largely elusive. Lactadherin, a secreted glycoprotein of milk-fat globule, is expressed by multiple cell types of arterial wall including ECs. Our previous proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…11,12,17) In this study, we observed that GSPB2 significantly prevented the obesity in db/db mice. GSPB2 also prevented the elevation in the levels of serum AGEs observed in db/db mice, suggesting an anti-non-enzymatic glycation effect of GSPB2.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…11,12,17) In this study, we observed that GSPB2 significantly prevented the obesity in db/db mice. GSPB2 also prevented the elevation in the levels of serum AGEs observed in db/db mice, suggesting an anti-non-enzymatic glycation effect of GSPB2.…”
Section: Discussionsupporting
confidence: 59%
“…[8][9][10] Dimeric procyanidin B2 is one of the main components of GSPE, which is more powerful than other polyphenols. Our previous data showed that grape seed procyanidin B2 (GSPB2) could prevent AGEs-induced ROS generation, proliferation and migration of human aortic smooth muscle cells, and alleviate diabetic arterial damage, [11][12][13] but little is known about its protective effects on diabetic cardiomyopathy.…”
mentioning
confidence: 99%
“…One of the major AGEs adducts, NΔ-(carboxymethyl) lysine, is formed from MGO (Thornalley, 1996). In endothelial cells, increased levels of AGEs cause oxidative stress, mitochondrial dysfunction, cellular dysfunction, and, ultimately, cell death (Li et al ., 2011). That hypericin inhibits the formation of AGEs suggests that it can ameliorate AGEs-related endothelial cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, not only has MFG-E8 expression emerged as a molecular hallmark of adverse cardiovascular remodeling with aging [2, 3, 13, 14], but MFG-E8 signaling has also been found to mediate the vascular outcomes of cellular and matrix responses to the hostile stresses associated with hypertension, diabetes, and atherosclerosis [15–19]. Increased MFG-E8 signaling promotes endothelial prothrombosis and triggers EC apoptosis, thus contributing to a disruption of the endothelium [20, 21], an enhancement of VSMC proliferation and invasion, as well as the deposition and amyloidization of the extracellular matrix [14, 21–31]. …”
Section: Introductionmentioning
confidence: 99%